The information technology of construction neurosimulator of the assessment of systems of safety - Пилькевич, Игорь Анатолиевич; Лобанчикова, Надежда Николаевна; Котков, Владимир Иванович; Коткова, Татьяна Николаевна (Eastern-European Journal of Enterprise Technologies, 2013)
The use of modern information technologies can facilitate information processing and automate decision-making processes of experts in information security. The aim of the research is to develop the information technology of predicting the reliability of information security system activation for the automation of information security experts’ work. The object of the study is the process of constructing intelligent systems of analysis and decision support. The subjects of the study are models, methods and tools for building the intelligent systems of analysis and decision support in order to predict the reliability of security systems activation, automation of information processing by experts. The information technology of development and implementation of the neurosimulator for predicting the reliability assessment of security systems and automation of the information security expert’s work in order to minimize the time for data processing and decision-making is described in the paper. The information technology can be used to predict a wide range of problems. The advantage of the proposed technology is the use of several variants of the activation function and network training methods, which allows to obtain a set of data for a thorough analysis and increase the objectivity of decision-making.